HUMAN MODELING IN THE IRAQI PRESS: (A Survey of Human Modeling for March And April 2011) - al-Shjeery, Suham (ALBAHITH ALALAMI, 2013)
This research deals with what so called concept of The Human Model and how Iraqi Media concerns of this concept practically as it plays a key role in attracting readers, on the first hand. On the second, it is important to shed light on the scientific desire of the Iraqi Media and how it deals with this contemporary trend especially in editorial media. The importance of the research stems from the fact that it alerts to a new stream of modern trends in journalistic writing, according to many modern Arab and foreign media studies; and to the importance of employing human modeling in dealing with facts, events, issues and problems in various editorial arts within their effective influence in conciliation. If this trend can contribute to the use of the largest number of readers to follow the events and benefit from the use of human modeling in the delivering the required media message. This study has ended by many conclusions: The Iraqi press has embraced human modeling in social subjects rather than in other political and cultural issues. The art of the column as the most prominent art employing human modeling was adopted. Then, it followed by the art of investigative journalism. Next, the art of news report, followed by articles in order. Iraqi Media has adopted this concept especially in dealing with social events more than any other ones, i. e.; political and cultural. In principle, the study used columns to functionalize this concept. And, in a way or another, it also used features, stories and essays. Emphasizing the use of known and unknown human models, as well as the employment of men and women of various functions and practical names, as models for the presentation of problems and events and facts and use them within the various press arts, in order to woo the reader towards this issue or that. This allowed readers to follow the issue or the incident without boredom, but recommends fans to use human modeling in journalistic writing should be taken care of and used in order to persuade the reader towards this event or that problem positively or negatively.